1990
DOI: 10.1073/pnas.87.7.2838
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid up-regulation of high-affinity interleukin 6 receptors on human epithelial cells.

Abstract: Interleukin 6 (IL-6) is a potent pleiotropic cytokine, known, among others, to stimulate immunoglobulin production by B cells and to trigger acute-phase protein synthesis by hepatocytes. Similar to IL-1, it is produced by monocytes and macrophages following an inlamator challenge. Analysis ofIL-6 receptor (IL-6R) expression on different human cell lines indicates that dexamethasone could upregulate the number of IL-6R on one epithelial cell line (UAC) and on two hepatoma cell lines (HepG2 and Hep3B). This effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
61
0
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(66 citation statements)
references
References 42 publications
4
61
0
1
Order By: Relevance
“…When SFs were pretreated with the glucocorticoid dexamethasone (dex), addition of IL-6 alone activated STAT DNA binding (Fig. 1B), consistent with previous results that cell surface expression of IL-6R␣ is induced by glucocorticoids (41). The induction of cellular responsiveness to IL-6 by the potent immunosuppressive agent dex is consistent with an anti-inflammatory action of IL-6 on SFs.…”
Section: Activation Of the Jak-stat Signal Transduction Pathway By Ilsupporting
confidence: 77%
“…When SFs were pretreated with the glucocorticoid dexamethasone (dex), addition of IL-6 alone activated STAT DNA binding (Fig. 1B), consistent with previous results that cell surface expression of IL-6R␣ is induced by glucocorticoids (41). The induction of cellular responsiveness to IL-6 by the potent immunosuppressive agent dex is consistent with an anti-inflammatory action of IL-6 on SFs.…”
Section: Activation Of the Jak-stat Signal Transduction Pathway By Ilsupporting
confidence: 77%
“…In various inflammatory states elevated glucocorticoid levels are observed. We and others have described that gpg0-mgNA as well as the functional protein is induced by glucocorticoids and not by IL-6 [18,19]. In the present study, evidence is presented that IL-6 and in parti.…”
Section: Discussionsupporting
confidence: 61%
“…Therefore, the regulation of the hepatic 80 kDa-IL-6-R subunit has been studied. It was found that glucocorticoids, but not IL-6 up-regulated mRNA as well as functional protein expression of gp80 [18,19]. Thus far, nothing is known about the regulation of the second subunit of the hepatic IL-6-R (gp130).…”
Section: Il-6 Is a Multifunctional Eytokine Involved Inmentioning
confidence: 99%
“…In this regard, pretreatment of humans with cortisol prior to endotoxin increased circulating concentrations of TNFα and IL-6 (46). Furthermore, glucocorticoids act synergistically with either cytokines or endotoxin to increase other diverse inflammatory mediators, such toll-like receptor-2 mRNA and protein (47), IL-6 receptor number (48), and under some conditions the acute-phase protein response (49).…”
Section: Discussionmentioning
confidence: 99%